Does Economic Policy Uncertainty Affect M&A Operations? Evidence from the Brazilian Market - Alexandre Teixeira Norberto Batista; Wagner Moura Lamounier; Poueri do Carmo Mário (BBR: Brazilian Business Review)
The objective of this work was to investigate the effect of Economic Policy Uncertainty on Mergers and Acquisitions operations of listed companies in Brazil. For this purpose, we have run a binomial logistic regression model to verify the impact of Economic Policy Uncertainty on the propensity for Mergers and Acquisitions in the following year. Using a sample of 128 publicly traded non-financial companies, from 2010 to 2018, we identified that Economic Policy Uncertainty reduces the propensity of acquiring firms to engage in Mergers and Acquisitions activities. The alternative metric used as a proxy for uncertainty, the Economic Uncertainty Indicator - Brazil, was not statistically significant. The results are consistent with international evidence. This study proposes a hybrid model that can be used to estimate the propensity for Mergers and Acquisitions in other contexts. Furthermore, it contributes to a series of emerging discussions on factors triggered by economic policy uncertainty that can alter the dynamics of corporate decisions.